Reduction of Patient Wait Time at a Multi-Specialty Hospital using DMAIC Methodology and Factor Analysis - Mahesh, BP; Soragaon, Bhimasen; R Annigeri, Anandkumar (International Journal of Engineering and Technology, 2018)
In medicine, cardiology is a very crucial specialization, as sometimes sudden deaths occur if there is no periodic check performed. Cardiology deals with disorder of hearts including the circulatory system. Physicians specialized in cardiology are cardiologists, and pediatricians specialized in cardiology are Pediatric cardiologists. In this paper, cardiology department concerning with adult patients is considered for the study; the out-patient section is taken up in specific. It is noticed that the patient wait time at the cardiology department of a small private hospital in Bangalore city, India, is very high; sometimes the wait time is almost about one hour. The patient wait time data has been collected; statistical analysis has been carried out; brainstorming and cause and effect diagram have been constructed to determine sub-causes and root causes of longer patient wait time. Also, a new schedule for treating cardiac patients has been developed to reduce the wait time.Â Â